Differences in Post-Delivery Blood Pressures Between Women Who Will Develop Postpartum Preeclampsia and Controls [12M]. (May 2020) - Brubaker, Laura H.; Brawley, Amalia M.; Williamson, Mary H.; Stetter, Christy M.; Kunselmanl, Allen R.; Pauli, Jaimey M.
Abstract : INTRODUCTION: Postpartum preeclampsia (with first clinical manifestation after delivery) is poorly understood but has the potential for catastrophic consequences for patients. Predictive variables in the postpartum period may improve outcomes. The purpose of this study was to determine if there is a difference in blood pressure in the immediate postpartum period (delivery to discharge) in women readmitted with postpartum preeclampsia and controls. METHODS: Deliveries in a 5-year interval (2014-2019) at a university hospital were included in this retrospective cohort study (n=3, 621 unique patients). IRB committee waiver was obtained for the study. Exclusion criteria were diagnosis of preeclampsia, eclampsia, or Hemolysis Elevated Liver Enzymes Low Platelets (HELLP) prior to delivery. Cases included readmissions for preeclampsia, eclampsia, or HELLP diagnosed after delivery (n=26). Controls were randomized from remaining patients (3:1 controls to cases, inflated by 10% to account for prevalence of exclusion criteria) (n=78). Each subject's highest systolic (SBP) and diastolic blood pressure (DBP) from delivery until discharge was recorded. Two sample t-tests were used, significance set at 0.05. RESULTS: The mean peak SBP for cases was significantly higher than controls at 147.4 mmHg (SD 13.4 mmHg) compared to 133.3 mmHg (SD 12.0 mmHg) ( P< .001). Mean peak DBP for cases was also higher than controls at 91.6 mmHg (SD 8.7 mmHg) compared to 82.9 mmHg (SD 8.0) ( P< .001). CONCLUSION: Blood pressure in the immediate postpartum period was higher in women readmitted for postpartum preeclampsia compared to controls. This information may be a first step in developing a predictive model to better understand and predict postpartum preeclampsia.